A Review on Traditional Risk Factors and Coronary Angiographic Findings between Younger and Older patients of Coronary Heart disease - Shrestha, MP; Siddique, MA; Ahmed, MK; Haque, KMHS S (University Heart Journal, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Ischemic heart disease (IHD) or Coronary Heart Disease (CHD) is a generic designation for a group of closely related syndromes resulting from myocardial ischemia. It comprises of stable angina, unstable angina, acute myocardial infarction and sudden death. Since the most common cause of IHD is coronary artery as a plaque of atheromatous deposits. It is often accompanied by atheromatous manifestations elsewhere in the body. It is a major cause of morbidity and mortality in the developed countries and its prevalence is rising in the developing countries. Though its prevalence is higher in developed countries, it has gained considerable attention in developing countries due to its rising trend and change in life style of the urban population. Association of risk factors with causation of coronary artery disease in young population also appears to be stronger. Compared to elderly. This is true particularly with regards to certain specific risk factors like BMI, Raised BP, LDL, TG and smoking. It is a pathological entity characterized by presence of intimal lesions called fibrofatty streaks or atheromas which protrude into and obstruct the vascular lumen. When it occurs, it involves almost every vascular bed and can produce myriads of manifestations of which Coronary artery disease is the most clinically significant. It starts at an early age as fatty streaks and then evolves into more complex atheromatous and fibro atheromatous lesion. Atherosclerosis leading to Coronary Heart Disease (CHD) is complex in origin. Involved in the pathogenesis of atherosclerosis are hemodynamic, throombotic, carbohydrate- lipid metabolic variables along with intrinsic characterization of arterial wall. These physiologic and biochemical factors underlie the clinical events that may eventually occur. Environmental factors such as smoking and sedentary life style also contribute to this process. The progression of atherosclerotic disease and increasing severity of atherosclerosis risk factors but also to the persistence of risk factors over time. Premature Coronary Artery Disease (CAD) is defined as CAD occurring below 65 years in women and 55 years in men. CAD in young is defined as CAD occurring in patient University Heart Journal Vol.4(1) January 2008